Kombinasi Pembuatan Pupuk Cair Organik dari Limbah Jeroan Ikan Tongkol (Euthynnus affinis) dengan Probiotik sebagai Upaya Optimalisasi Pertumbuhan Tanaman - Ichsanul Mukmin; Dyah Ayu Banowati; Phagy Fathoni Putri; Resti Putri Mustika; Rezky Amanda Ningsih; Madyasta Anggana Rarassari (Seminar Nasional Lahan Suboptimal, 2021)
Mukmin I, Banowati DA, Putri PF, Mustika RP, Ningsih RA, Rarassari MA. 2021. The combination of making organic liquid fertilizer from the offal waste of tuna fish (Euthynnus affinis) with probiotics as an effort to optimize plant growth. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembng 20 Oktober 2021. pp. 660-669. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tuna fish (Euthynnus affinis) was a type of pelagic fish that had economic value. Catching dan managing tuna produced waste that was directly discharged into the environment, resulting in unpleasant odors dan causing the environment to became polluted. One alternative way was that the waste could be utilized by making liquid organic fertilizer. This study aimed to utilize the waste of tuna fish innards (Euthynus affinis) using the EM4 fermentation method which could be an alternative to liquid organic fertilizer for plant fertility. The writing method in this study used study of literature. The results of this study showed that addition of liquid organic fertilizer from fermented waste fish gave the enhancement nutrition for the soil. The increase in nutrient levels in the soil triggered an increase in lateral root length, stem diameter, fresh weight dan dry plant weight. The application of organic liquid fertilizer from fermented fish made effects on increasing soil porosity, reducing soil density dan triggering the production of auxin substances that increase lateral root growth. Therefore, the manufacture of organic liquid fertilizer from fermented tuna (Euthynnus affinis) accelerated plant growth dan along with its used could reduce fish offal waste.